Importance of HPV in Chinese Penile Cancer: A Contemporary Multicenter Study - Gu, Weijie; Zhang, Peipei; Zhang, Guiming; Zhou, Jiaquan; Ding, Xuefei; Wang, Qifeng; Wang, Beihe; Wei, Yu; Jin, Shengming; Ye, Dingwei; Zhu, Yao (Frontiers in Oncology, 2020)
Objective To investigate the HPV DNA prevalence and genotype distribution among penile cancer in China. To identify association between HPV prevalence, different histological subtypes, tumor stage, tumor grade, demographics, comorbidity and phimosis incidence trend. Standardized HPV DNA detection and p16INK4a expression were used in a multi-center series of 340 penile squamous cell carcinomas diagnosed from 2006-2017. Materials and Methods HPV DNA detection and genotyping were examined by a validated kit for 23 different HPV subtypes (PCR-RDB HPV test). The cases with positive HPV DNA were additional tested for p16INK4a expression to confirm the HPV infection. Results Using the PCR-RDB HPV test, overall HPV prevalence was 48.8% (166/340) and that of p16INK4a expression was 45.6%. In this studied population, HPV16 was the most frequent HPV type detected in HPV-positive cancers (76.5%). HPV18 was the second most common type in penile cancers (15.1%). After pathology review, 307 cases were confirmed as invasive penile cancer, and the other 33 were non-invasive caners. The histologic subtypes of warty, basaloid, clear cell papillary, adenosquamaous and pseudohyperplastic were showed high HPV DNA prevalence. Among invasive cancers, no statistically significant differences in prevalence were observed by tumor grade, tumor stage or lymphnode stage at diagnosis. HPV positive penile cancer incidence significantly increase and the phimosis incidence significantly decrease from 2006 to 2017. Conclusions About a half of penile cancers were related to HPV infection. Our findings highlight the phimosis related penile cancers have been declining, the HPV related in the development of penile cancer and a fully aware of regional differences in HPV genotype distribution are tasks for penile cancer control and prevention.